Understanding Pragmatics and Pragmatic Competence in ELT Materials - Nurdiana Nurdiana (Universitas Bunda Mulia, 2019)
Pragmatics is a branch of linguistics concerned with utterance and speaker meaning. With regard to English language teaching (ELT) materials, pragmatics may deal with function in English or language functions—that is what or which language expression commonly used in particular situations. Speaking about function, there are some pragmatic aspects which we should be knowledgeable of. The present paper attempts to discuss what the pragmatic aspects are and their significance in the teaching of language functions through ELT materials. To discuss these pragmatic aspects, a library research was deployed by referring to previous studies on pragmatics and pragmatic competence in language teaching, including the author’s investigation on pragmatics in ELT materials. The results indicate that it is imperative for English language teachers to understand pragmatics in ELT materials as it helps them to teach language functions which are pragmatically effective or functional.Keywords: language functions, sociopragmatics, pragmalinguistics, meta-pragmatic information, ELT materials